Kointik: Eksplorasi Auditif dan Notasi Grafis dalam Penciptaan Musik Eksperimental Berbasis Bunyi Koin - Sulastri, Salas; Apriani, Arni; Setiaji, Deden (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study presents an experimental music composition on sound eksploration from a single object: the metal coin. Entitled Kointik (Koin Tekstur Intuitif Komposisi), the work applies an intuitive and purely auditory approach, focusing on the exploration of texture, rhythm, and sound dynamics. The composition is constructed entirely between the body and the coin object. A set of graphic and symbolic notations was developed contextually to represet sound qualities, silences, gestures, and dramaturgical structures. The result reveal that everyday objects like coins possess strong musical and symbolic potential when treated as artistic materials. This work produces not only an immersive listening experience but also opens reflective space in value, social pressure, and the meaning of silence. Kointik contributes to the development of experimental music rooted in sensory experience and the curtular significance of local object.